2021
DOI: 10.4196/kjpp.2021.25.6.497
|View full text |Cite
|
Sign up to set email alerts
|

Depilatory creams increase the number of hair follicles, and dermal fibroblasts expressing interleukin-6, tumor necrosis factor-α, and tumor necrosis factor-β in mouse skin

Abstract: Author contributions: P.F.T. and F.P.C. performed most of the experiments, analyzed the data and wrote the draft. T.S.Y. conducted the animal experiment, collected the specimens and helped with data analysis. H.J.L. and C.T.C. contributed to study conception, experimental design and manuscript writing. All authors have approved the final manuscript for publication and agreed to be accountable for all aspects of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…They work by breaking down the sulphur bonds in the hair's keratin that are sensitive to strong alkaline and deoxidation agents. The active ingredient for deoxidizing the sulphur bonds is a salt of thioglycolic acid (Tsai et al, 2021). Chemical depilation generally does not destroy the dermal papilla, and hair is able to grow back afterwards, because relatively small amounts of chemicals are used (Pohl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They work by breaking down the sulphur bonds in the hair's keratin that are sensitive to strong alkaline and deoxidation agents. The active ingredient for deoxidizing the sulphur bonds is a salt of thioglycolic acid (Tsai et al, 2021). Chemical depilation generally does not destroy the dermal papilla, and hair is able to grow back afterwards, because relatively small amounts of chemicals are used (Pohl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They work by breaking down the sulphur bonds in the hair's keratin that are sensitive to strong alkaline and deoxidation agents. The active ingredient for deoxidizing the sulphur bonds is a salt of thioglycolic acid (Tsai et al, 2021). Chemical depilation generally does not destroy the dermal papilla, and hair is able to grow back afterwards, because relatively small amounts of chemicals are used (Pohl et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The data suggested that sodium sulfide made a significant impact on healing, compared with depilatory cream and physical depilation methods. Furthermore, it has been reported recently that compared with shaving methods, commercially available depilatory creams caused a transient minor inflammatory response of the skin and increased the levels of cytokines that might subsequently affect hair growth but increased the number of hair follicles [ 40 ]. Coincidentally, this can also be observed in Figure 3 D in the present study.…”
Section: Discussionmentioning
confidence: 99%